Assessment of optical, mechanical and nonlinear properties of potassium acid phthalate single crystal: a potential candidate for optoelectronic applications. (13th January 2020) - Kumari, Manju; Vijayan, N; Nayak, Debabrata; Kumar, Mahesh; Gupta, Govind; Pant, R P
Abstract: A good optical quality semi-organic single crystal of Potassium Acid Phthalate (KAP) was harvested from aqueous solution by using slow evaporation solution growth technique (SEST) at ambient condition. The defect free single crystal of KAP was analyzed by different instrumentation techniques, for checking its compatibility for different applications. Its unit cell dimensions and phase purity was examined by powder X-ray diffraction (PXRD) and found that it crystallizes in orthorhombic with non-centrosymmetric in nature. The quality of the grown ingot was assessed by high resolution X-ray diffraction (HRXRD) technique and found that, the crystalline quality is better with less grain boundaries. Its optical properties were scrutinized by UV–vis., photoluminescence (PL) and time resolved photoluminescence (TRPL) measurements respectively. The mechanical stability of the grown crystal was tested by Vickers microhardness method and found that the grown crystal shows indentation size effect (ISE) which was explained using different theoretical models. Its third order nonlinear optical properties were studied by Z-scan measurement by using Ti:Sapphire laser as a source and determined its nonlinear absorption coefficient ( β ) and it was found that the KAP crystal is one of the preferable choices for optical limiting applications.